2004
DOI: 10.1007/s00280-003-0732-7
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme expression profiles suggest the novel tumor-activated fluoropyrimidine carbamate capecitabine (Xeloda) might be effective against papillary thyroid cancers of children and young adults

Abstract: We conclude that the majority of differentiated thyroid cancers (74%) express TP and low levels of TS (63% undetectable). The results support the hypothesis that capecitabine is activated in the majority of differentiated thyroid cancers and that 32% have favorable expression of all three enzymes (TP, TS, and DPD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…S-1 is converted into fluorouracil after P r e p r i n t 12 internalization into cells, and S-1 shares similar anticancer properties as intravenous 5-Fu [34].The clinical study of 84 patients with advanced gastric cancer showed that the progression free survival (PFS) of patients was overtly longer in the Apatinib + S-1(a fluorouracil drug) group than that in S-1 group [35]. Capecitabine is a novel drug that can be well absorbed after oral administration, and converted into 5-FU by thymidine phosphorylase in tumor tissues [36]. Capecitabine has been confirmed to replace 5-FU for the gastrointestinal chemoradiation therapy [37].…”
Section: Discussionmentioning
confidence: 99%
“…S-1 is converted into fluorouracil after P r e p r i n t 12 internalization into cells, and S-1 shares similar anticancer properties as intravenous 5-Fu [34].The clinical study of 84 patients with advanced gastric cancer showed that the progression free survival (PFS) of patients was overtly longer in the Apatinib + S-1(a fluorouracil drug) group than that in S-1 group [35]. Capecitabine is a novel drug that can be well absorbed after oral administration, and converted into 5-FU by thymidine phosphorylase in tumor tissues [36]. Capecitabine has been confirmed to replace 5-FU for the gastrointestinal chemoradiation therapy [37].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its mechanism of action, it is suspected that high levels of thymidine phosphorylase and low thymidylate synthetase and dihydropyrimidine dehydrogenase would predict response to capecitabine. In one study looking at immunohistochemistry of thyroid tumors, 43% of PTC and 25% of FTC had favorable characteristics (Patel et al 2004).…”
Section: Chemotherapeutic Agentsmentioning
confidence: 99%
“…Patient MTC samples have not been analyzed in detail for the enzyme expression pattern so far. FTTiv-derived cells had favorable profile according to the data by Patel et al (40), but they are not responsive to 5FU treatment in general. The link between expression as predictive markers and the therapeutic response is more complex (22).…”
mentioning
confidence: 93%
“…Favorable enzyme profiles (high TP and low DPD) should generate high intratumor levels of 5FU that are effective against many tumors, especially those with low TS. A total of 32% of papillary thyroid cancers exhibited this profile, and therefore the authors suggested them to be sensitive to 5FUbased treatment (40). Patient MTC samples have not been analyzed in detail for the enzyme expression pattern so far.…”
mentioning
confidence: 99%